2018
DOI: 10.1002/etc.4286
|View full text |Cite
|
Sign up to set email alerts
|

Biotransport of metallic trace elements from marine to terrestrial ecosystems by seabirds

Abstract: Physical systems, such as currents and winds, have traditionally been considered responsible for transporting contaminants. Although evidence is mounting that animals play a role in this process through their movements, we still know little about how such contaminant biotransport occurs and the extent of effects at deposition sites. In the present study, we address this question by studying how rhinoceros auklets (Cerorhinca monocerata), a seabird that occurs in immense colonies (∼300 000 pairs at our study si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…These metals are often the focus of other environmental pollutant studies as they are well known for their toxicity, ability to bioaccumulate in organisms and their persistence and longevity in the environment (Šerić Jelaska et al, 2014). Many studies demonstrated the impact of pollutant laden guano on recipient environments by measuring metal concentrations in soils, vegetation and invertebrates, with results showing higher contaminant levels in samples from colonies compared to samples from control sites (Headley, 1996; Santamans et al, 2017; Shoji et al, 2019). Furthermore, of the few papers that did explore POP transport by seabirds, the majority of papers established a similar pattern, with higher concentrations of POPs in soils and organisms within colonies in comparison to areas without seabirds (Choy et al, 2010; Evenset et al, 2004; Foster et al, 2011; Roosens et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metals are often the focus of other environmental pollutant studies as they are well known for their toxicity, ability to bioaccumulate in organisms and their persistence and longevity in the environment (Šerić Jelaska et al, 2014). Many studies demonstrated the impact of pollutant laden guano on recipient environments by measuring metal concentrations in soils, vegetation and invertebrates, with results showing higher contaminant levels in samples from colonies compared to samples from control sites (Headley, 1996; Santamans et al, 2017; Shoji et al, 2019). Furthermore, of the few papers that did explore POP transport by seabirds, the majority of papers established a similar pattern, with higher concentrations of POPs in soils and organisms within colonies in comparison to areas without seabirds (Choy et al, 2010; Evenset et al, 2004; Foster et al, 2011; Roosens et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This ‘guanotrophication’, or seabird‐induced eutrophication, occurs when the level of nutrients added to a system exceeds what is required (Signa et al, 2015). As apex predators, many seabirds also exhibit high contaminant loads due to biomagnification and bioaccumulation along the marine food chain (Shoji et al, 2019). Chemicals, including persistent organic pollutants (POPs) and trace elements, can pass through individuals via feathers, eggs and guano (Furness & Camphuysen, 1997; Otero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They reported high concentrations of Ag and Co in two ponds that were affected by Arctic terns and common eiders, respectively. A recent study by Shoji et al (2018) documented that Co was enriched in auklet-affected sites as well. All these studies suggest that seabirds could exert impacts on the distribution of Ag and Co within their colonies.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 98%
“…A number of studies have elucidated that birds could transfer various nutrient and metal elements. For example, a group of metals and metalloids in sediments have been identified as seabird-related elements Shoji et al, 2018;Sun et al, 2000). P in soil or sediments is a marker for seabird influence (Adame et al, 2015;.…”
Section: Source Of Ag and Co In The Bulk Sediments Of Zs2mentioning
confidence: 99%
“…Geolocator tagging revealed that the rhinoceros auklet is very widely distributed throughout the year in continental shelf waters of the temperate North Pacific Ocean. Within this realm, rhinoceros auklets are vulnerable to a wide variety of anthropogenic stressors including oiling at sea [125,126], bycatch in fishing gear [127][128][129], and chemical contamination of food webs [130][131][132][133]. They are also affected by oceanographic change [100,134].…”
Section: Conservation Implicationsmentioning
confidence: 99%